Slotted Carrier Sense Multiple Access Protocols- A Review - Kaur, Kulbir; Kumar, Kiran (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
CSMA/CA protocols rely on the random deferment of packet transmissions. Like most other protocols, CSMA/CA was designed with the assumption that the nodes would play by the rules. This is important the nodes themselves control deferment. However, with the higher programmability of the network adapters, the temptation to tamper with the software or firmware is likely to grow; in this way, a user could obtain a much larger share of the available bandwidth at the expenseof other users. This paper focuses on slotted CSMA/CA and tries to find out its limitations of the slotted CSMA/CA protocols.